THE WAYS OF USING CONSTRUCTIVISM TO TEACHING PHRASEOLOGICAL UNITS AND VOCABULARY FOR EFL (Academicia Globe: Inderscience Research, 2022)
This article is dedicated to the study of the English phraseology units and typology of two languages which presents a certain interest both for theoretical investigation and for practical usage.